O eixo sino-americano e a inserç\~ao externa brasileira: Antes e depois da crise - Eduardo Costa Pinto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This article has two main objectives. First, to develop, in a stylized way, a characterization line of the recent transformations that took place in the international economic and political system in the first decade of the 21st century, trying to show that these changes are a product of the new configuration of the Sino-American axis of international power and wealth accumulation. Second, to show that the positive impacts of such new axis to Brazilian economy, mostly from 2003 to 2009, were also accompanied by possible negative effects in the long run associated to the regressive specialization of Brazilian export profile and to the national industrial structure. Data have revealed that there are threats and opportunities to Brazilian external insertion in the actual international context; however, such process is not still clear due to the recent economic crisis. Therefore, in order to think the Brazilian international insertion in the long run, it is necessary to deepen the discussion about the impacts of Sino-American axis after the crisis.
Keywords: F50; F42; O54; 330